ИСЛАМ КАРИМОВ: МӘНАЎИЯТ- ИНСАН КӨЗҚАРАСЛАРЫНЫҢ ӨЛШЕМИ - Абаев, С.; Якубов, М. (FAN va JAMIYAT, 2017)
The article deals with the essense and practical significance of the category of spirituality, worked out in the books of the first President of the Republic of Uzbekistan Islam Karimov. There has been analysed the spiritual-educational value of this category.